IBU BINTARI; Breastfeeding education to improve skilss of post partum - Vitria Komala Sari; Seli Angraini; Vedjia Medhyna (Universitas Aisyiyah Yogyakarta, 2025)
Exclusive breastfeeding is the fulfillment of nutrition given to infants aged 0 to 6 months. The coverage of Exclusive Breastfeeding at Tigo Baleh Community Health Center is 56.5%. The cause of the problem that often occurs is that mothers do not have the ability to breastfeed properly. The impact on babies who are not breastfed will be susceptible to health problems. One of the supporting media for mothers to understand breastfeeding techniques is by using pocket books. The purpose of this study was to determine the effect of providing pocket books on skills in postpartum mothers in the Tigo Baleh Community Health Center Working Area, Bukittinggi City in 2024. This research method is quantitative. using a quasi-experimental design with two groups, namely pretest and posttest with a sample of 32 postpartum women and breastfeeding mothers. The sample of postpartum women with a total sample of 32 people consisting of 16 intervention groups and 16 control groups with purposive sampling technique. The instruments used were questionnaires and checklists. Research data processing uses SPSS with Wilcoxon and Mann-Whitney. The study results showed a difference in pretest-posttest skill scores of 0.000 (p<0.05) in the intervention group, while there was no difference in results in the control group, with a result of 0.002 (p>0.05). The conclusion of this study is that providing a pocket book has an effect on breastfeeding knowledge, skills, and self-efficacy among postpartum mothers in the Tigo Baleh Community Health Center (Puskesmas) working area in Bukittinggi City. It is hoped that the study site can utilize the pocket book in providing education to postpartum and breastfeeding mothers to improve breastfeeding skills.